CONTEXTUAL MARKETING IN THE ELECTRONIC COMMERCE MARKET - ZHYLINSKA, Oksana; FIRSOVA, Svitlana (Herald of Khmelnytskyi National University. Economic sciences, 2023)
It has been shown that online business creates new professions and opens up new work places. A persistent trend of growth and development of electronic commerce may occur in Ukraine, driven by growth drivers: increasing Internet penetration; an increase in the number of smartphones sold in Ukraine; outbreak caused by COVID-19; growing trust in digital payment systems; increased variety and improvement of payment methods; expansion of delivery geography and shorter delivery terms; low delivery rate; growth of individual living; increasing reliability of online sellers; development of innovative technologies (augmented reality, virtual reality). The main prospects and insecurities are outlined, such as the worldwide digitalization and their influx into online business and the economy. The rise of contextual marketing in the e-commerce market has been promoted with the help of such technologies as the Internet of speech (IoT) and piece intelligence (AI), which can be used to collect per-line inputs from their clients on the basis of individual approach, creating a personalized client profile. It has been proven that custom marketing can operate on three levels: informational marketing, interactive marketing, and intrinsic marketing.The combination of these three levels of customized marketing includes the creation of personalized customer satisfaction “responsive and responsive” and the promotion of more targeted marketing based on mobile apps, theft payment systems, piece intelligence, which will gradually lead to the development of digitalization, the introduction of digital products through the method of satisfaction and maximization participants in the electronic commerce market.
Keywords: contextual marketing; electronic commerce market; Intern et of speeches; piece intelligence; digital growth; online business; digitalization; EPS (electronic payment system)